High‐frequency ultrasonography but not 930‐nm optical coherence tomography reliably evaluates melanoma thickness in vivo: a prospective validation study. (30th September 2014) - Meyer, N.; Lauwers‐Cances, V.; Lourari, S.; Laurent, J.; Konstantinou, M.‐P.; Lagarde, J.‐M.; Krief, B.; Batatia, H.; Lamant, L.; Paul, C.
Summary Background Early diagnosis and rapid surgical excision are essential for improving the prognosis of patients with melanoma. Reflectance confocal microscopy has been validated as a feasible procedure for in vivo diagnosis of melanoma but cannot be used to measure tumour thickness. However, ultrasonography and optical coherence tomography may allow melanoma thickness to be measured in vivo. Objectives To validate the accuracy and reliability of high‐frequency ultrasonography (HFUS) and optical coherence tomography for assessing melanoma thickness in vivo. Methods We conducted a prospective study on 131 patients with at least one equivocal melanocytic lesion. Each lesion underwent optical coherence tomography and HFUS assessment, followed by excision and pathological examination. Histopathology was considered to be the gold standard for assessing melanoma thickness. Repeatability, inter‐ and intrarater reproducibility and reliability were evaluated for each imaging procedure. Results Ultrasonography showed a good level of agreement with histology [intraclass correlation coefficient (ICC) 0·807; 95% confidence interval (CI) 0·703–0·877] and excellent inter‐rater reproducibility (G = 0·97), resulting in reliable in vivo assessment of melanoma thickness. The 930‐nm optical coherence tomography showed a poor level of agreement with histopathology (ICC 0·0; 95% CI −0·2–0·2) and the inter‐rater reproducibility was null (G = 0·00). Conclusions HFUS is a reliable and reproducible noninvasive method for assessing melanoma thickness. Routine use of HFUS may allow single‐step excision of equivocal melanocytic lesions, with surgical margins determined by in vivo assessment of tumour thickness.